"La Corte y sus presidencias": la Corte Enrique Santiago Petracchi i, de Paula Gaido y Laura Clérico - Fernandez Fiks, Tomas (2022)
"The Court Enrique Santiago Petracchi I is the title of the third installment of the collection "The Court and its presidencies", directed by Paula Gaido and Laura Clérico. This anthology proposes a novel approach to the study of the Argentine Supreme Court, taking as a starting point the return\nof democracy in 1983..."